RELEVANSI PEMIKIRAN KH. AHMAD DAHLAN TERHADAP PENDIDIKAN AGAMA ISLAM DI ERA 4.0 - Bayu Suta Wardianto (IAIN Purwokerto, 2020)
The industrial revolution was an inevitable oversize. This industrial revolution resulted in a real change in human life, both social change, lifestyle, and also in the education sector. In Islamic religious education, change and development are also happening. In this concept, a thought from the nation's leader, K.H Ahmad Dahlan, provides a conception of Islamic religious education that is still relevant to be used in this 4.0 era. The type of research used in this research is descriptive qualitative research and in the type of classification of this research is by library research techniques, data researched in the form of books and literature sourced from literature. The result of this research is the connection between islamic religious education thinking according to K.H Ahmad Dahlan with the changes and development of the era in the era of 4.0 that basically a Muslim should be able to cooperate between religion, culture, the progress of civilization of a changing age, freedom in thinking, the dynamics of life and the role of human beings in his life must be based on the Qur'an and Hadith